Islamic financial instruments and its practices in Islamic Banking / Nurdinie Nabihah Noryamal - Noryamal, Nurdinie Nabihah (2019)
The existence and development of Islamic banking and finance in industry are mainly to avoid the prominent prohibited elements include riba or pre-determined rate of interest, gharar or ambiguity in contracts, maysir or known as gambling and monopoly. Thus, Islamic financial instruments become the savior to avoid from applying them in Islamic banking’s operation. The purpose of this study is to identify the instruments and the process of the contracts according to the products from Bank Islam Malaysia Berhad and Bank Rakyat. This study also aims to clarify the differences base rates of each product offered by BIMB and Bank Rakyat. This study used interview method for primary data while for secondary method are by library research, internet browsing and textual analysis. This study concluded that the application of Islamic financial instrument can be varied between BIMB and Bank Rakyat due to the current practices.